Use of genetically engineered stem cells for glioma therapy - NAMBA, HIROKI (Oncol Lett, 2016)
Glioblastoma, the most common and most malignant type of primary brain tumor, is associated with poor prognosis, even when treated using combined therapies, including surgery followed by concomitant radiotherapy with temozolomide-based chemotherapy. The invasive nature of this type of tumor is a major reason underlying treatment failure. The tumor-tropic ability of neural and mesenchymal stem cells offers an alternative therapeutic approach, where these cells may be used as vehicles for the invasion of tumors. Stem cell-based therapy is particularly attractive due to its tumor selectivity, meaning that the stem cells are able to target tumor cells without harming healthy brain tissue, as well as the extensive tumor tropism of stem cells when delivering anti-tumor substances, even to distant tumor microsatellites. Stem cells have previously been used to deliver cytokine genes, suicide genes and oncolytic viruses. The present review will summarize current trends in experimental studies of stem cell-based gene therapy against gliomas, and discuss the potential concerns for translating these promising strategies into clinical use.